Evaluation of the metabolic activity, angiogenic impacts, and GSK-3β signaling of the synthetic cannabinoid MMB-2201 on human cerebral microvascular endothelial cells - Laith Naser AL-Eitan; Saif Zuhair Alahmad; Sufyan Ali Ajeen; Ahmad Younis Altawil; Iliya Yacoub Khair; Hana Salah Abu Kharmah; Mansour Abdullah Alghamdi (Journal of Cannabis Research)
Abstract Angiogenesis is an intrinsic physiological process involving the formation of new capillaries from existing ones. Synthetic cannabinoids refer to a class of human-made chemicals that are primarily designed to mimic the effects of delta-9-tetrahydrocannabinol, the primary psychoactive compound in cannabis. Studies investigating the association between synthetic cannabinoids and cellular reactions are limited, and the available scientific evidence is insufficient. Consequently, the primary goal was to examine the effects of the synthetic cannabinoid MDMB-2201 on brain angiogenesis in vitro to provide a comprehensive analysis of MMB-2201’s potential therapeutic or adverse effects on vascular development and related health conditions. Human Cerebral Microvascular Endothelial Cells (HBEC-5i) were incubated with MMB-2201, and their metabolic activity, migration rate, and tubular structure formation were examined. Expression levels of several angiogenesis-related proteins such as vascular endothelial growth factor (VEGF), Angiopoietin-1 (ANG-1), and Angiopoietin-2 (ANG-2) were assessed using western blot, ELISA, and real-time PCR. Furthermore, the phosphorylation of glycogen synthase kinase 3 beta (GSK-3β) at Ser9 induced by MMB-2201 was evaluated. HBEC-5i cells showed a significant increase in metabolic rate, enhanced migration, and sprouting of brain endothelial cells. Moreover, there was a noticeable increase in the mRNA and protein levels of VEGF, ANG-1, and ANG-2, as well as in the phosphorylation rate of GSK-3β at Ser9. This study paves the way for a novel pharmacological approach to addressing various angiogenesis-related diseases by targeting cannabinoid receptor type-1. Further exploration using different antagonists or agonists of cannabinoid receptors, depending on the specific characteristics of the disorders, may be necessary.